Factors influencing a patient's decision to choose the type of treatment to improve dental esthetics - Gržić Renata; Špalj Stjepan; Lajnert Vlatka; Glavičić Snježana; Uhač Ivone; Kovačević-Pavičić Daniela (Vojnosanitetski Pregled)
Backgroung/Aim. Interest in dental esthetics has increased rapidly during the last few decades among both patients and dentists, and the creation of a natural dental appearance has become an important task in all fields of dentistry, especially in prosthodontics and restorative dentistry. The aim of this research was to investigate factors influencing a patient's decision to choose the type of treatment to improve dental esthetics. Methods. A total of 700 Caucasian subjects participated in the crosssectional study (261 men, 439 women, aged 18-86 years, mean age 46.2 ± 18.6). The study included clinical examination and a self-administrated questionnaire based on self-perceived esthetics, satisfaction with the appearance of their maxillary anterior teeth and previous dental experience. Multiple logistic regression was used in statistical analysis. Results. Hiding teeth during smile was the most important predictor for choosing fixed prosthetic restorations (OR 9.1), followed by self-perceived bad fixed prosthesis, malpositioned teeth and female gender (OR 2.9, 2.4, and 1.5, respectively). The increase in satisfaction with dental appearance and previous orthodontic therapy reduced chances for seeking prosthetic therapy (each OR 0.4). The significant predictors for bleaching choosing were hiding teeth during smiling, already done bleaching, female gender, lower levels of satisfaction with dental appearance and the absence of the previous orthodontic therapy (OR 5.8, 2.4, 1.8, 0.5 and 0.4, respecitively). Hiding teeth during smile, self-perceived malposition and crowding, and lower levels of satisfaction, were significant predictors for choosing orthodontic treatment (OR 3.1, 2.4, 2.2 and 0.6, respectively). None of current dental statuses was statistically significant predictor for choosing prosthodontic, bleeching nor orthodontic therapy. Conclusion. The psychological elements and female gender are the main predictors of seeking dental therapy. Understanding the prevalence of dissatisfaction with the present esthetics and desired treatments to improve esthetics can be a guide for strategies for intervention to improve esthetics.